Pengaruh Bahasa Pemrograman Scratch pada Mata Pelajaran Informatika untuk Meningkatkan Self Efficacy Siswa Kelas VIII di SMP 8 Padang (Indo-MathEdu Intellectuals Journal, 2024)
The importance of learning Informatics is not only limited to mastering techniques and practical skills in technology development, but also in forming students' self-efficacy or self-confidence in overcoming challenges and solving problems in the digital world. This study aims to analyze the influence of Scratch programming language on informatics subjects to improve the self-efficacy of grade VIII students at SMP 8 Padang. This type of research is quantitative research with an experimental method. The design used in this research is a Quasi Experimental Design in the form of a Nonequivalent Control Group Design. The data collection technique used is a Likert scale questionnaire. The experimental group used the scratch programming language with a total of 32 students, and the control group used the blookly programming language with a total of 32 students. For hypothesis testing, this study uses t-test statistics with a significant level of 5% (= 0.05) and N-Gain test. The results of the study showed that the use of scratch programming language influenced the self-efficacy of grade VIII students of SMP 8 Padang with a significance value of 0.001. This means a significant t-value (p = 0.001 < 0.005). In the N-Gain analysis, the experimental class experienced an increase in self-efficacy score of 0.54 (medium category), while the control class only 0.07 (low category)